Response of selenoproteins gene expression profile to mercuric chloride exposure in chicken kidney. (December 2020) - Chu, Jia-Hong; Yan, Yu-Xue; Gao, Pei-Chao; Chen, Xue-Wei; Fan, Rui-Feng
Abstract: Kidney is a primary target organ for mercuric chloride (HgCl2 ) toxicity. Selenium (Se) can exert antagonistic effect on heavy metals–induced organ toxicity by regulating the expression of selenoproteins. The objective of this study was to investigate the effect of HgCl2 on the gene expression of selenoproteins in chicken kidney. Sixty male Hyline brown chickens were randomly and evenly divided into two groups. After acclimatization for one week, chickens were provided with the standard diet as well as non-treated water (CON group), and standard diet as well as HgCl2 -treated water (250 ppm, HgCl2 group). After seven weeks, kidney tissues were collected to examine the mRNA expression levels of 25 selenoproteins genes and protein expression levels of 4 selenoproteins. Moreover, correlation analysis and principal component analysis (PCA) were used to analyze the expression patterns of 25 selenoproteins. The results showed that HgCl2 exposure significantly decreased the mRNA expression of Glutathione peroxidase 1 (GPX1), GPX4, Thioredoxin reductase 2 (TXNRD2), Iodothyronine deiodinase 1 (DIO1), Methionine-Rsulfoxide reductase 1 (SELR), 15-kDa selenoprotein (SEP15), selenoprotein I (SELI), SELK, SELM, SELN, SELP, SELS, SELT, SELW, and SEPHS2. Meanwhile, HgCl2 exposure significantly increased the mRNA expression of GPX3, TXNRD1, and SELU. Western blot analysis showed that the expression levels of GPX3, TXNRD1, SELK, and SELN were concordant with these mRNA expression levels. Analysis results of selenoproteins expression patterns showed that HgCl2 -induced the main disorder expression of selenoproteins with antioxidant activity and endoplasmic reticulum resident selenoproteins. In conclusion, selenoproteins respond to HgCl2 exposure in a characteristic manner in chicken kidney. Highlights: Selenoproteins respond to HgCl2 exposure in a characteristic manner. HgCl2 -induced the disorder expression of selenoproteins with antioxidant activity. HgCl2 -induced the disorder expression of ER resident selenoproteins.